Proceedings of the 3rd International Symposium of Quantum Beam Science at Ibaraki University "Quantum Beam Science in Biology A 2019
DOI: 10.7566/jpscp.25.011008
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Life Science by Use of Muon Spin Spectroscopy: With a View to Monitoring Protein Functions

Abstract: Approaches by means of muon spin spectroscopy in the bioscience field began by determining reaction rates of biomacromolecule components with muonium, and then the labelled electron method, using positive muons, was applied to proteins and DNA to monitor the electron transfer processes. Currently, the muon stopping sites in proteins are being determined. In addition, newly started or planned experiments to monitor biological function by use of muon spin spectroscopy have also been introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Torikai et al [11] and Hubbard et al [21] reported the electron transfer in DNA [11]. There are other trials on amino acids and peptide bonds to understand the stopping site of muon and electron transfer mechanism [22]. Kiyotani et al [23] also reported some trials to understand the electron and proton transfer in enzime reactions.…”
Section: Sr In Biomolecules 41 Experimentsmentioning
confidence: 99%
“…Torikai et al [11] and Hubbard et al [21] reported the electron transfer in DNA [11]. There are other trials on amino acids and peptide bonds to understand the stopping site of muon and electron transfer mechanism [22]. Kiyotani et al [23] also reported some trials to understand the electron and proton transfer in enzime reactions.…”
Section: Sr In Biomolecules 41 Experimentsmentioning
confidence: 99%
“…Recently SR method pointed out its application for cancer research [14] and diagnosis of disease [24]. Electron transfer in protein [17,25] and photosynthesis processes have been studying intensively through experimentally and theoretically [26,27]. Besides accelerator produced muon, cosmic muons are also useful for the study of non-destructive analysis of large scale architectures [28] and characterization of materials like study of trapped radioactive materials [29].…”
Section: Applications Of Conventional Muonsmentioning
confidence: 99%